Effect of kinesio taping on performance in counter-movement jump - Kümmel, J.; Mauz, D.; Blab, F.; Vieten, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to identify the influence of taping with a flexible tape on jumping performance and its effects on the impulse in a stretch-shortening cycle movement. 23 subjects were divided in control group and intervention group. The subjects participated in two trials of vertical counter-movement jumps. In the trial, the knee extensors of the subjects in the intervention group were taped with an activating taping technique. Reaction forces of the jump were measured with an AMTI-force plate. Results showed no significant differences.